FACTORS AFFECTING PROFITABILITY IN INFRASTRUCTURE COMPANIES LISTED ON IDX - Riyanto, Vanessa Josephine; Susanto, Liana (Graduate Program of Universitas Tarumanagara, 2024)
This study aims to determine the factors that can affect profitability in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) during 2020-2022. This research was conducted using three independent variables consisting of company leverage, company size, and company liquidity. The company leverage variable is proxied through the DAR (Debt to Asset Ratio) ratio, the company size variable is proxied through the Log of Total Assets, and the company liquidity variable is proxied through the CR (Current Ratio) ratio. The profitability variable is proxied through the ROA (Return on Asset) ratio. The sample tested in this study was selected by purposive sampling method and the data used was valid data from 19 infrastructure sector companies. Data processing techniques in this study using multiple regression analysis assisted by the SPSS (Statistical Product and Service Solution) program version 27 and Microsoft Excel. The results of the study showed that the leverage variable has a significant negative effect on profitability, the company size variable has a significant positive effect on profitability, and the liquidity variable has no significant effect on profitability. The implication of this research is the need for companies to optimally utilize existing assets and arrange good funding sources so that they can earn profits optimally and can increase the company's profitability value which will provide good signals for investors.